Self-reported pain among Cambodian Americans with depression: patient-provider communication as an overlooked social determinant - S. Megan Berthold; Richard Feinn; Angela Bermudez-Millan; Thomas Buckley; Orfeu M. Buxton; Sengly Kong; Theanvy Kuoch; Mary Scully; Tu Anh Ngo; Julie Wagner (SpringerOpen, 2022)
Plain English summary Pain is a common health problem among torture survivors and refugees. Clear communication about one's pain supports timely and precise diagnosis and treatment. The relationship between communication with health providers and pain is understudied. We examined whether Cambodian American refugees' reports of difficulty communicating with their health care provider was associated with their reports of pain. We analyzed data collected by Cambodian community health workers from a sample of 186 Cambodian American adults with depression who did not have diabetes. More than three quarters were female with an average age of 55 years and an average of almost seven years of education. About one-third had private insurance and two-thirds could not speak English conversationally. A little more than a third reported no pain at all. There were multiple factors associated with higher reported pain scores including: greater difficulty understanding healthcare provider, depressive symptoms, trauma symptoms, food insecurity, and social isolation. Those who reported lower pain scores had more education, higher income, spoke English more fluently, had more social support, were working, and had private insurance. When we analyzed the influence of all of these factors together, only difficulty understanding one's healthcare provider and depressive symptoms predicted level of pain. Difficulty communicating with the healthcare provider is a factor that can be addressed with intervention to improve health and reduce pain. Healthcare institutions should be supported with necessary resources, such as trained community health workers, to secure patients' rights to be able to communicate with their health providers.